The Impact of Tax Law 7/2021 on the Indonesian Stock Market: Pre and Post Analysis - Adeline Colinkang; Yani Permatasari (Jurnal Riset Akuntansi dan Keuangan, 2024)
This study aims to obtain empirical evidence of the stock market's reaction regarding the enactment of Tax Harmonization Law Number 7 of 2021 by the Ministry of Finance of the Republic of Indonesia towards companies listed on the Indonesia Stock Exchange (IDX) in the tax year 2022. The research method employed is the Wilcoxon Signed-Rank test to compare the market's reaction 10 days before and 10 days after the enactment date of the Tax Harmonization Regulation Law (THRL), which was implemented at the beginning of 2022, namely January 1, 2022. The research sample consists of 696 companies listed on the Indonesia Stock Exchange (IDX). The results indicate a negative difference in market reaction before and after the enforcement of the THRL, as seen from the Cumulative Abnormal Return (CAR) and Average Trading Volume Activity (ATVA) variables. This is possibly due to market participants' uncertainty in acting after the enactment of the new THRL.